Understanding variation in salamander ionomes: A nutrient balance approach. (10th December 2018) - Prater, Clay; Scott, David E.; Lance, Stacey L.; Nunziata, Schyler O.; Sherman, Ryan; Tomczyk, Nathan; Capps, Krista A.; Jeyasingh, Punidan D.
Abstract: Ecological stoichiometry uses information on a few key biological elements (C, N and P) to explain complex ecological patterns. Although factors driving variation in these elements are well established, expanding stoichiometric principles to explore dynamics of the many other essential elements comprising biological tissues (i.e. the ionome) is needed to determine their metabolic relationships and better understand biological control of elemental flows through ecosystems. In this paper, we report observations of ionomic variation in two species of salamander ( Ambystoma opacum and A. talpoideum ) across ontogenic stages using specimens from biological collections of two wetlands sampled over a 30‐year period. This unique data set allowed us to explore the extent of ionomic variation between species, among ontogenic stages, between sites and through time. We found species‐ and, to a lesser extent, site‐specific differences in C, N and P along with 13 other elements forming salamander ionomes but saw no evidence of temporal changes. Salamander ionomic composition was most strongly related to ontogeny with relatively higher concentrations of many elements in adult males (i.e. Ca, P, S, Mg, Zn and Cu) compared to metamorphic juveniles, which had greater amounts of C, Fe and Mn. In addition to patterns of individual elements, covariance among elements was used to construct multi‐elemental nutrient balances, which revealed differences in salamander elemental composition between species and sites and changes in elemental proportions across ontogenic development. These multi‐elemental balances distinguished among species‐site‐ontogenic stage groups better than using only C, N and P. Overall, this study highlights the responsiveness of consumer ionomes to life‐history and environmental variation while reflecting underlying relationships among elements tied to biological function. As such, ionomic studies can provide important insights into factors shaping consumer elemental composition and for predicting how these changes might affect higher‐order ecological processes.